2009
DOI: 10.1016/j.ypmed.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of maintenance-tailored therapy (MTT) and standard behavior therapy (SBT) for the treatment of obesity

Abstract: Objective-To evaluate a maintenance-tailored therapy (MTT) compared to standard behavior therapy (SBT) for treatment of obesity. Main outcome measure: change in body weight. Results-Mean (SD) weight losses at 6, 12, and 18 months were 5.7 (5.0) kg, 8.2 (8.6) kg and 8.3 (8.9) kg for MTT and 7.4 (3.9) kg, 10.7 (8.2) kg and 9.3 (8.8) kg for SBT. Total weight loss did not differ by group at 18 months, but the time pattern differed significantly (p < .001). The SBT group lost more weight in the first 6 months. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 30 publications
3
64
1
2
Order By: Relevance
“…For 7 of these studies, the percentage of weight loss could not be calculated, but a significant absolute weight loss-weight maintenance was reported Itoh et al 2001;Jeffery et al 2009;Kuller et al 2006Kuller et al , 2007Kuller et al , 2012Leermakers et al 1999;Tanumihardjo et al 2009;Wolfson et al 2010;Yankura et al 2008;Yatsuya et al 2011) and thus, these studies were retained. The majority of retained studies (n = 20) reported that participant weight was measured by study staff.…”
Section: Weight-loss and Weight-maintenance Combined Studies (N = 24)mentioning
confidence: 99%
See 3 more Smart Citations
“…For 7 of these studies, the percentage of weight loss could not be calculated, but a significant absolute weight loss-weight maintenance was reported Itoh et al 2001;Jeffery et al 2009;Kuller et al 2006Kuller et al , 2007Kuller et al , 2012Leermakers et al 1999;Tanumihardjo et al 2009;Wolfson et al 2010;Yankura et al 2008;Yatsuya et al 2011) and thus, these studies were retained. The majority of retained studies (n = 20) reported that participant weight was measured by study staff.…”
Section: Weight-loss and Weight-maintenance Combined Studies (N = 24)mentioning
confidence: 99%
“…The lengths of the interventions were found to be variable among studies: 15 weeks ), 18 weeks (McLaughlin et al 2008, 21 weeks (Christiansen et al 2007), 3 months Ditschuneit and Flechtner-Mors 2001;Ditschuneit et al 1999Ditschuneit et al , 2002Flechtner-Mors et al 2000;Foreyt et al 1993;Itoh et al 2001;Morgan et al 2009Morgan et al , 2011Tanumihardjo et al 2009), 4 months Layman et al 2009;Thorpe et al 2008), 6 months (Gold et al 2007;Jeffery et al 2009;Krukowski et al 2008;Kuller et al 2006Kuller et al , 2007Kuller et al , 2012Leermakers et al 1999;Matvienko and Hoehns 2009;Rock et al 2007;Rolls et al 2005;West et al 2011;Wing et al 2010;Wolfson et al 2010;Yankura et al 2008;Yatsuya et al 2011), and 12 months Burke et al 2008;Teixeira et al 2010). These time periods were considered to reflect the weight-loss phase, because the intervention either ended or was reduced considerably.…”
Section: Weight-loss and Weight-maintenance Combined Studies (N = 24)mentioning
confidence: 99%
See 2 more Smart Citations
“…Individual; Groups and Families) typically taught in MSW programs. The current preferred treatment for obesity is behavior therapy (Jeffery et al, 2009) that includes frequent monitoring of diet and exercise and outlines specific weight loss goals. In utilizing obesity-focused case situations social worker students can learn the behavioral strategies of weight loss programs (including long term follow up and support) while applying the basic techniques of behavioral therapy.…”
Section: Practice Sequencementioning
confidence: 99%